v-K-ras leads to preferential farnesylation of p21(ras) in FRTL-5 cells: Multiple interference with the isoprenoid pathway - Laezza, Chiara (The National Academy of Sciences, 1998)
The isoprenoid pathway in FRTL-5 thyroid cells was found to be deeply altered on transformation with v-K-ras. A dramatic overall reduction of protein prenylation was found in v-K-ras-transformed cells in comparison with the parent FRTL-5 cells, as shown by labeling cells with [(3)H]mevalonic acid. This phenomenon was accompanied by a relative increase of p21(ras) farnesylation and by a decrease of the ratio between the amounts of geranylgeraniol and farnesol bound to prenylated proteins. Analysis of protein prenylation in FRTL-5 cells transformed by a temperature-sensitive mutant of the v-K-ras oncogene indicated that these variations represent an early and specific marker of active K-ras. Conversely, FRTL-5 cells transformed with Harvey-ras showed a pattern of [(3)H]-mevalonate (MVA)-labeled proteins similar to that of nontransformed cells. The K-ras oncogene activation also resulted in an overall decrease of [(3)H]-MVA incorporation into isopentenyl-tRNA together with an increase of unprocessed [(3)H]-MVA and no alteration in [(3)H]-MVA uptake. The effects of v-K-ras on protein prenylation could be mimicked in FRTL-5 cells by lowering the concentration of exogenous [(3)H]-MVA whereas increasing the [(3)H]-MVA concentration did not revert the alterations observed in transformed cells. Accordingly, v-K-ras expression was found to: (i) down-regulate mevalonate kinase; (ii) induce farnesyl-pyrophosphate synthase expression; and (iii) augment protein farnesyltransferase but not protein geranylgeranyl-transferase-I activity. Among these events, mevalonate kinase down-regulation appeared to be related strictly to differential protein prenylation. This study represents an example of how expression of the v-K-ras oncogene, through multiple interferences with the isoprenoid metabolic pathway, may result in the preferential farnesylation of the ras oncogene product p21(ras).